Vitamin D Deficiency: A New and Unexpected Concern in Men's Health Status - Atabay, Shamsadin; Tabasi, Shabnam; Hojjati, Mohammad Taher (Archives of Men's Health, 2025)
Introduction: Vitamin D deficiency represents a significant public health concern associated with various acute and chronic diseases. Emerging evidence suggests that vitamin D may influence iron metabolism and erythropoiesis through multiple pathways. This study aimed to investigate the relationship between vitamin D status, gender differences, and hematological parameters in an Iranian population. Methods: This cross-sectional study included 275 participants (95 men, 180 women) aged 18-70 years. Exclusion criteria comprised chronic diseases, malignancies, and use of iron/vitamin D supplements. Comprehensive hematological and biochemical analyses were performed using standardized methods, including HPLC for vitamin D quantification. Results: Mean vitamin D levels were significantly lower in men compared to women (26.53 ± 11.14 vs 30.51 ± 14.43 nmol/L). Vitamin D deficiency was more prevalent in men (63.4%) than in women (50%). A paradoxical inverse relationship was observed between vitamin D status and hemoglobin levels, with deficient individuals showing higher hemoglobin concentrations (13.68 ± 1.53 vs 13.19 ± 0.62 g/dL). No significant associations were found between vitamin D levels and conventional iron status markers. Conclusion: Our findings reveal a higher prevalence of vitamin D deficiency in men compared to women, challenging conventional assumptions about gender distribution of vitamin D status. The unexpected inverse relationship between vitamin D and hemoglobin levels suggests complex physiological interactions that warrant further investigation. These results highlight vitamin D deficiency as an emerging concern in men's health that requires greater clinical attention.